Chemical potential and biomedical activity of gold nanoparticles in cancer and drug delivery systems: an updat - Soni, Sandeep Kumar; Solanki, Dr. Manoj Kumar (Vietnam Journal of Science and Technology, 2024)
Gold nanoparticles (AuNPs) are broadly utilized in medical fields because of its unique potential, biomedical activity and physicochemical properties. The biocompatible nature, optical properties, and minor cytotoxicity are the key features of AuNPs which make them valuable for biomedical applications. Today, AuNPs are widely used for cancer therapy, bioimaging, biosensing, radiotherapy, photodynamic therapy and drug delivery system. The present article illustrates the current progress in AuNPs synthesis, properties of AuNPs, various biomedical activity of AuNPs in therapeutic fields and drug delivery systems. Apart from numerous benefits the chemically synthesized AuNPs also creates certain level of toxicity in the living system which represents confronts of AuNPs against biomedical applications. Reducing its cytotoxic nature and development of green AuNPs can led to development of new history in field of medical science and clinical trials. Thus, the present review article deals with the compiled study of various fundamental research over AuNPs such as its chemical and bio-synthesis, biomedical and therapeutic applications viz. plasmonic photothermal therapy, photodynamic therapy, folate receptor targeting, targeted drug delivery etc. The article also finds some of its confronts against biomedical application because of its cytotoxic nature and its possible future prospects.